The marine leech Stibarobdella loricata (Harding, 1924) (Hirudinea, Piscicolidae), parasitic on the angel shark Squatina spp. and sandtiger shark Carcharias taurus Rafinesque, 1810 (Chondrichthyes: Squatinidae, Carchariidae) in Southern Brazilian waters - Soto J. M. R. (Brazilian Journal of Biology, 2003)
The presence of the marine leech, Stibarobdella loricata (Harding, 1924) (Hirudinea, Piscicolidae), is reported on the southern coast of Brazil, based on seven lots with 47 specimens, between 71 and 182 mm in total length, collected on the dorsal region of angel sharks, Squatina argentina (Marini, 1930); S. guggenheim Marini, 1936; S. punctata Marini, 1936 (Chondrichthyes, Squatinidae); and on the head of a sandtiger shark, Carcharias taurus Rafinesque, 1810 (Chondrichthyes, Carchariidae). This is the first record of S. loricata in the western Atlantic and of its parasitic association with S. argentina, S. guggenheim, S. punctata, and C. taurus.